Hemi‐ablative low‐dose‐rate prostate brachytherapy for unilateral localised prostate cancer. (23rd December 2019) - Langley, Stephen; Uribe, Jennifer; Uribe‐Lewis, Santiago; Franklin, Adrian; Perna, Carla; Horton, Alex; Cunningham, Melanie; Higgins, Donna; Deering, Claire; Khaksar, Sara; Laing, Robert
Abstract : Objectives: To report clinical outcomes of the Hemi‐Ablative Prostate Brachytherapy (HAPpy) trial evaluating treatment‐related toxicity and effectiveness of hemi‐gland (HG) low‐dose‐rate (LDR) prostate brachytherapy as a focal approach to control unilateral localised prostate cancer. Patients and Methods: Single institution phase IIS pilot study of patients treated with focal 4D Brachytherapy™ (BXTAccelyon, Burnham, Buckinghamshire, UK). The primary outcome was patient‐reported toxicity 24 months after implant. The secondary outcome was assessment of disease control. Outcomes in HG patients were compared to whole‐gland (WG) controls obtained from our prospective cohort registry by negative binomial and linear regression models. Results: Pre‐treatment demography was similar between the 30 HG patients and 362 WG controls. Post‐implant dosimetry was similar for the prostate gland target volumes and significantly reduced for the urethra and bowel in HG patients relative to WG controls, but this did not translate into a difference in post‐implant mean symptom scores between the two groups. Nevertheless, the change in score from baseline indicated that the impact on pre‐treatment symptom status was less after HG implants. Only HG patients showed a return to baseline urinary scores as early as 12 months. Sexual potency was conserved in 73% and 67% of HG and WG patients, respectively ( P  = 0.84). Post‐implant prostate‐specific antigen (PSA) kinetics revealed that baseline PSA was reduced at 24 months by 78% and 88% in HG and WG patients, respectively ( P  < 0.05). Treatment relapse occurred in one (3%) HG patient 55 months after implant and in nine (3%) WG patients at 32–67 months after implant. Conclusion: This pilot study suggests that treatment‐related toxicity and biochemical outcomes after HG implants are broadly similar to those observed with WG treatment despite the lower dose delivered by HG implants.